Philosophical Conception Of The Answers To The Question "Can one become a good teacher?" - BEMENA, Bruce bruce; Armand, Armand; TOTOHASINA, André (Journal of Research and Multidisciplinary, 2024)
In the context of teaching disciplines, whether in institutions not beyond high schools and universities, many people think that the provision of academic skills and intuitive knowledge are sufficient to face and / or ensure the job of teacher. It seems that to teach well, it would be enough to master your subject, to have disciplinary university knowledge to transmit. The rest would be innate, no doubt?... Strange job, which would not know professional "gestures", which would not require continuous training. Also, there is the problem of researching the relationships between all the educational knowledge necessary to ensure good transmission of knowledge to the learner who is perfectly suited to a very important subject. Currently, the very spectacular evolutions of technology are no longer a subject of discussion. This development sometimes diminishes listening skills for students in the classroom. This leads to the tendency towards the idea of ​​systematic rejection or neglect by learners of a discipline. What makes this paper exposes ideas necessary to inspire the general principles towards the didactic method applied by the teachers to make like its subject.